Ratchet effects in superconducting ring-shaped devices. (22nd August 2017) - Ji, Jiangdong; Jiang, Xingyu; Yuan, Jie; He, Ge; Jin, Biaobing; Zhu, Beiyi; Kong, Xiangdong; Jia, Xiaoqing; Kang, Lin; Xu, Weiwei; Chen, Jian; Jin, Kui; et al.
Abstract: The vortex ratchet effects in superconducting ring-shaped NbN devices are experimentally investigated. We have studied three types of samples: a narrowing eccentric circular loop, standard circular loop, and widening eccentric circular loop. Using the time-dependent Ginzburg–Landau simulations, we demonstrate that the sample edges significantly influence the dynamics of the vortices entering the samples. Through transport measurements with dc and ac currents, strong rectified voltage responses were observed for all the samples over a wide range of temperatures, critical currents, and magnetic fields. Moreover, there are some differences in the detailed ratchet behaviors among them. Furthermore, we also observed the ratchet effects in our samples caused by the current-induced field, which deserves further investigations.